Learning Direct and Inverse Proportion: A Study in the Framework of Pedagogical Content Knowledge - Ruli, Redo Martila; Jupri, Al; Dahlan, Jarnawi Afgani (Universitas Islam Negeri Sunan Kudus, 2025)
Many real-life problems are closely related to the concepts of direct and inverse proportion. Therefore, it is essential for students to develop a sound understanding of these concepts. This study aims to observe the mathematics learning process in the classroom, specifically in relation to pedagogical and content knowledge regarding direct and inverse proportion. This research employed a qualitative observational approach to examine how the teaching and learning process unfolds in the context of these mathematical concepts. The study took place on November 28, 2024, involving 28 seventh-grade students from a private junior high school in Bandung, Indonesia. Data were collected through direct classroom observation during the lesson. The primary research instrument was an observation sheet, which was developed to examine the implementation of Pedagogical Content Knowledge (PCK) in mathematics instruction. The data analysis process consisted of data processing, data analysis, and data interpretation. The observation of seventh-grade mathematics instruction focusing on the concepts of direct and inverse proportion from a PCK perspective provides insight into how PCK is applied in the mathematics classroom. The predominant use of lecture-based teaching limited students’ opportunities to construct conceptual understanding, resulting in noticeable difficulties in distinguishing between direct and inverse proportion problems. It was found that many students lacked a clear understanding of the differences between direct and inverse proportions, leading to difficulties in identifying whether a given problem involved one or the other. This indicates a need for instructional methods that allow students to construct their own understanding of the topic being taught. Furthermore, the development of instructional materials should be more closely aligned with students’ cognitive characteristics to support meaningful learning experiences. Permasalahan dalam kehidupan sehari-hari banyak sekali berkaitan dengan konsep perbandingan senilai dan berbalik nilai, oleh sebab itu perlu bagi siswa untuk memahami konsep ini. Penelitian ini bertujuan untuk mengamati proses pembelajaran matematika di dalam kelas yang ditinjau dari pedagogik dan pengetahuan tentang konten perbandingan senilai dan berbalik nilai. penelitian ini merupakan studi kualitatif observasional, metode ini digunakan untuk menyelidiki proses pembelajaran di kelas pada materi perbandingan senilai dan berbalik nilai. Penelitian ini dilaksanakan pada tanggal 28 November 2024, dengan partisipan yaitu 28 orang siswa kelas VII pada salah satu SMP swasta di Kota Bandung. Teknik pengumpulan data pada penelitian ini adalah dengan melakukan pengamatan langsung pada saat proses pembelajaran. Instrumen yang digunakan pada penelitian ini berupa lembar observasi yang dikembangkan untuk mengamati PCK pada pembelajaran di kelas. Teknik analisis data pada penelitian ini terdiri atas pemrosesan data, analisis data, dan interpretasi data Pembelajaran matematika kelas VII dengan konsep perbandingan senilai dan berbalik nilai yang ditinjau dari sudut pandang PCK memberikan gambaran tentang bagaimana PCK diterapkan dalam pembelajaran matematika di dalam kelas. Metode ceramah yang digunakan guru menimbulkan dampak yang membuat siswa kurang memaknai apa yang sedang dipelajari. Kurangnya pemahaman siswa tentang perbedaan antara konsep dari perbandingan senilai dan berbalik nilai yang mengakibatkan siswa tidak bisa membedakan permasalahan yang sedang dibahas apakah permasalahan perbandingan senilai atau perbandingan berbalik nilai. Diperlukan metode pembelajaran yang dapat membuat siswa membangun pengetahuannya sendiri tentang materi yang sedang dipelajari, Selain itu, pengembangan bahan ajar melalui proses penelusuran dan pengkajian yang lebih mendalam dan telah disesuaikan dengan karakteristik siswa, sehingga pada akhirnya siswa dapat memaknai apa yang sedang dipelajarinya.